Siapa Mendorong Pertumbuhan E-Commerce Daerah? Analisis Transformasi Spasial dan Demografi Pelaku Usaha di Provinsi Nusa Tenggara Barat - Jauhari, M. Agusnul (ALETHEIA: Jurnal Sosial & Humaniora, Inovasi, Ekonomi, dan Edukasi, 2025)
Digital transformation has restructured trade systems through the rapid expansion of platform-based e-commerce. However, such growth remains uneven across regions and business actors. This study aims to analyze the structural dynamics of e-commerce growth from a regional perspective and to identify the dominant demographic actors driving its acceleration. The core problem lies in digital adoption disparities and the limited body of research examining e-commerce from the supply-side perspective rather than consumer behavior. The study employs a quantitative-descriptive approach with a comparative-structural design using secondary data from Indonesia’s E-Commerce Statistics (2019–2024). Analytical techniques include descriptive-comparative analysis, growth analysis, and demographic structural analysis. Findings reveal a significant rise in e-commerce enterprises both nationally and in West Nusa Tenggara (NTB), although NTB remains in a catching-up phase with lower penetration. The regional business structure reflects coexistence between e-commerce and non-e-commerce, indicating a gradual hybrid transformation. Demographically, growth is not youth-dominated but concentrated among mature productive-age entrepreneurs transforming existing businesses into digital platforms. This study identifies a dual transformation pattern—regional acceleration and generational adaptation—as its novelty. It concludes that the future of regional e-commerce depends on digital infrastructure convergence and cross-generational capacity building. Policy recommendations emphasize connectivity expansion, MSME digital incubation, and marketplace ecosystem integration.